Creating an inclusive leisure space: strategies used to engage children with and without disabilities in the arts-mediated program Spiral Garden. Issue 2 (16th January 2018) - Smart, Eric; Edwards, Brydne; Kingsnorth, Shauna; Sheffe, Sarah; Curran, C J; Pinto, Madhu; Crossman, Shannon; King, Gillian
Abstract: Purpose: This article describes how service providers use a set of practical strategies to create an inclusive leisure space in Spiral Garden, an arts-mediated outdoor summer day program for children with and without disabilities. Methods: This study was guided by an interpretive qualitative approach. Fourteen Spiral Garden service providers participated in semi-structured interviews. Nine had extensive experience with the program and had been present during key phases of program development spanning over a 26-year period and five were service providers during the summer of 2013. Transcript data were analyzed using inductive thematic analysis. Results: The analysis produced eight strategies organized under three larger categories that service providers perceived to be essential in creating an inclusive leisure space: (1) engaging children in collective experiences; (2) encouraging peer interactions and friendships; and (3) facilitating collaborative child-directed experiences. Conclusions: Service providers working across different inclusive settings can use findings from this study to contribute to program design and implementation. Presented strategies enable children to experience opportunities for spontaneous free play, individualized structured support, and meaningful social participation. Overall, service providers are encouraged to enhance supportive child and service provider relationships and reciprocal child and environment relationships in group-based programs. Implications for Rehabilitation: Exploring and facilitating reciprocal relationships between children and their environment is essential to creating inclusive leisure spaces. Transforming program intentions of meaningful social participation into practice requires learning about and affecting change in children's individual social contexts. Service providers can engage themselves as full participants in inclusive leisure spaces through playful negotiations, internal reflections, and artistic expressions.